2021
DOI: 10.1111/echo.14974
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term prognostic value of right ventricular function in patients with first acute ST elevation myocardial infarction treated by primary angioplasty

Abstract: Introduction Limited data are known about the prognostic value of right ventricle (RV) function in patients with first acute ST‐segment elevation myocardial infarction (STEMI). The aim of this study was to investigate the prognostic value of RV dysfunction in predicting both in‐hospital and long‐term outcomes in these patients, irrespective of the site of necrosis. Methods We enrolled 502 consecutive patients with first acute STEMI treated with primary angioplasty and underwent echocardiography within 48 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…RV free wall LS has emerged as a prognostic factor offering additional prognostic value beyond clinical and echocardiographic data [26]. RV dysfunction assessed by the conventional echocardiographic parameters of RV and RV free wall LS was an independent outcome predictor in an unselected group of 502 STEMI patients [27]. RV GLS has only been assessed in a cohort of 282 patients with inferior STEMI, where it emerged as an independent predictor of MACE, even after adjusting for multiple covariates [28].…”
Section: Discussion and Expected Resultsmentioning
confidence: 99%
“…RV free wall LS has emerged as a prognostic factor offering additional prognostic value beyond clinical and echocardiographic data [26]. RV dysfunction assessed by the conventional echocardiographic parameters of RV and RV free wall LS was an independent outcome predictor in an unselected group of 502 STEMI patients [27]. RV GLS has only been assessed in a cohort of 282 patients with inferior STEMI, where it emerged as an independent predictor of MACE, even after adjusting for multiple covariates [28].…”
Section: Discussion and Expected Resultsmentioning
confidence: 99%
“…RVLS > −22% was proved to be superior that TAPSE in the multivariate model. The research that included 520 AMI patients treated with PCI showed that FAC < 35%, TAPSE < 17 mm, RVLS > −17%, s' < 9.5 cm/s, RVMPI > 0.43, and tricuspid regurgitation velocity >2.8 m/s were strong independent predictors of in-hospital MACE and 1-year mortality [70]. Figure 1 (Panel F) demonstrates echocardiography-derived RVLS in patient after AMI.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…2 However, STEMI patients are still at risk for long-term adverse cardiovascular events (MACEs). 3 Studies have shown that current smoking, history of heart failure, and diabetes mellitus are independent predictors of MACEs after STEMI. 4,5 SII and NT-proBNP levels are rarely reported to be associated with MACEs.…”
Section: Introductionmentioning
confidence: 99%